EPEN-10. ROLE OF DNA METHYLATION ANALYSIS IN RECURRENT PAEDIATRIC EPENDYMOMA. Issue 2 (22nd June 2018) - Rogers, Hazel A; Ritzmann, Timothy A; Paine, Simon ML; Storer, Lisa D; Pajtler, Kristian W; Sill, Martin; Donson, Andrew M; Foreman, Nicholas K; Kool, Marcel; Pfister, Stefan M; Grundy, Richard G
Abstract: Ependymoma is the second most common malignant brain tumour in children. Relapse occurs in approximately 50% cases and is associated with a very poor prognosis. Recent studies highlighted the importance of DNA methylation in ependymoma. However, less is understood of its role at relapse. DNA methylation profiles were generated for 146 primary and 118 recurrent ependymoma samples using the Infinium HumanMethylation450 BeadChip arrays (Illumina). Samples were classified into previously defined subgroups with only 9 (6%) primary samples assigned to non-ependymoma groups. There was no significant difference in relapse risk between EPN_PFA and EPN_RELA cases. However, EPN_RELA cases relapsed significantly quicker. There was also no significant difference in survival between EPN_PFA and EPN_RELA relapsed cases. Radiotherapy given at relapse was associated with a significant improvement in survival for EPN_PFA cases but not EPN_RELA cases, although the number of cases investigated was low, limiting statistical power. The number of cases available for other ependymoma subgroups was too low for statistical analysis. However, in line with previous publications, EPN_PFB and EPN_SPINE cases displayed low relapse rates compared to other subgroups. 55 primary and matched relapsed cases were profiled. 53/55 (96%) cases, remained in the same subgroup at first relapse. Statistical comparisons suggested a low level of significant alterations in methylation levels at specific genes between primary and matched recurrent samples. In conclusion, relapse rates were very similar between common paediatric molecular subgroups and prognosis for relapsed cases was poor for all cases. Subgroups remained stable at relapse with little change in methylation levels.